Single crystal growth of BaZrO3 from the melt at 2700 °C using optical floating zone technique and growth prospects from BaB2O4 flux at 1350 °C. Issue 3 (14th December 2018) - Xin, Cong; Veber, Philippe; Guennou, Mael; Toulouse, Constance; Valle, Nathalie; Ciomaga Hatnean, Monica; Balakrishnan, Geetha; Haumont, Raphael; Saint Martin, Romuald; Velazquez, Matias; Maillard, Alain; Rytz, Daniel; et al.
Abstract : Growth of BaZrO3 crystals at 2700 °C in a mirror furnace and growth prospects at 1350 °C using BaB2 O4 flux are reported. Abstract : We report the growth of BaZrO3 single crystals by the optical floating zone technique and the investigation on its flux growth using BaB2 O4 as a solvent. 6 mm long colorless and transparent single crystals were obtained with a mirror furnace without the need for post-treatment annealing. Its properties are determined and compared with those of two commercial crystals grown by the tri-arc Czochralski method. The chemical composition was investigated using glow discharge mass spectrometry (GDMS) and secondary ion mass spectrometry (SIMS), which indicate minor impurities of Sr, Hf, Ca and Ti, with maximal concentrations for Sr and Hf in the range of 0.3–0.5% at. The optical band gap determined by UV-visible spectroscopy is found to be ∼4.8 eV and indicates the high quality of the BaZrO3 crystals grown by the optical floating zone technique. Raman spectroscopy at ambient conditions and at low temperatures down to 4.2 K reveals a relatively sharp second-order spectrum and does not reveal any structural phase transition. Prospective high-temperature solution growth using BaB2 O4 self-flux was investigated and led to 150–200 μm BaZrO3 crystals. This solvent opens the way to grow BaZrO3 at half its melting point by the flux method.